ENVIRONMENTALLY FRIENDLY CONSTRUCTION SITES: SUSTAINABILITY AND GREEN PRACTICES - Arici, Ayse (International Scientific Journal Vision, 2023)
Today, environmentally friendly practices and sustainability principles are gaining more and more importance in the construction industry. Resources are used intensively in this sector, and environmental impacts are high. Construction sites are at the heart of construction processes and have great potential for environmental sustainability. In this context, the management of construction sites per environmentally friendly practices and sustainability principles will reduce environmental impacts and contribute to the efficient use of resources. The building materials industry is an important component of the construction industry and plays a critical role in ensuring environmentally friendly practices. Factors such as selecting building materials, energy efficiency, waste management, and recycling are decisive for construction sites to adopt an environmentally friendly approach. Using sustainable building materials is an important step towards reducing environmental impacts and protecting resources. The purpose of this article is to encourage the management of construction sites following environmentally friendly practices and sustainability principles and to raise awareness in this area. The article aims to present strategic approaches for companies operating in the construction industry, engineers, architects, and other relevant stakeholders by emphasizing the importance of building materials and why the use of sustainable building materials is important. In this way, an important step will be taken to create environmentally friendly construction sites and make future construction projects less environmentally harmful.